2D train-track-bridge interaction analysis considering the effect of ballasted tracks - Tran Le Anh Duc; Phan Hoang Nam; Nguyen Van My; Tran Dinh Quang; Fabrizio Paolacci (Tạp chí Khoa học và Công nghệ)
This paper investigates the effect of ballasted tracks on the dynamic interaction between train, track, and bridge systems. A 2D interaction model is developed, incorporating detailed representations of the bridge, train, and track, with and without ballasted tracks. The Cat Linh - Ha Dong urban railway line on a simply supported bridge in Hanoi is used as a case study to perform parametric analysis, evaluating how variations in track parameters influence the dynamic responses of the bridge, train, and track. The numerical results reveal a significant dynamic vertical coupling between the bridge decks, highlighting the critical importance of including ballasted tracks in the modeling process of these structures.